The Effect of Pinna Position on Body Temperature Measurements Made with a Tympanic Membrane Thermometer in Pediatric Patients - Nilay Orkun; İsmet Eşer (Galenos Yayinevi, 2020)
Aim:The aim of this study was to investigate the effect of pinna position on body temperature measurements made with a tympanic membrane thermometer in pediatric patients.Materials and Methods:This study was conducted with a quasi-experimental design employing a pre-test and post-test. For analysis of the data, frequencies, percentages, means and standard deviations were calculated, and the significance of the difference between paired values was tested in order to investigate the effects of the auricle position on measurement values.Results:The age of the patients included in the study ranged between 6 and 13 years, and the mean age was 10.25±1.83 years. The mean difference between measurements in the two different positions was 0.35°C. The measurements made in each position were represented in a Bland Altman plot. It was seen that the differences between the two positions were not distributed around zero, but instead showed a systematic distribution around 0.35°C. There was a significant relationship between the differences and the mean values. The difference between the mean durations of the measurements was found to be 1.07 seconds longer with pinna positioning than without. The discomfort levels of the patients during temperature measurement without pinna positioning and with pinna positioning ranged between 0-2 and 0-4 according to the facial expressions scale respectively. During temperature measurement with pinna positioning and without pinna positioning, patients felt no discomfort.Conclusion:In measurements carried out using tympanic membrane thermometers in pediatric patients, positioning the auricle by pulling it downward posteriorly yielded more reliable and correct outcomes.